Legal Analysis of Enforcement of the Criminal Action of Defamation Through Social Media as Reviewed From the ITE Law and the KUHP: (Case Study of Decision Number: 415/Pid.Sus/2020/PN Tar) - Timbo Mangaranap Sirait; Adriansyah Halim (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
The crime of defamation can be divided into two forms: conventional and verbal. Conventional methods are usually implemented through direct statements or written media. This study aims to answer questions related to the Legal Review of Perpetrators of Criminal Acts of Defamation Through Social Media. First, the criminal liability of perpetrators of criminal acts of defamation through social media is based on Decision Number 415/Pid.Sus/2020/PN Tar. This study uses two types of data: primary legal materials and secondary legal materials. Primary legal materials include basic norms, basic rules, laws and regulations, and official documents or records. Secondary legal materials are obtained from literature such as books, legal journals, research results, and various other scientific works. The results of the study indicate, first, that criminal liability for perpetrators of defamation through social media in Decision Number 415/Pid.Sus/2020/PN Tar results in a two-month prison sentence with a six-month probation period, based on evidence and testimony presented at trial. Second, in issuing the verdict, the judge considered the Public Prosecutor's indictment, assessing both aggravating and mitigating factors for the defendant.